Statistics for Management / Seventh Edition - Levin Richard I; Rubin David S (Prentice Hall International, 1998)
Preface, Introduction, Grouping and Displaying Data to Convey Meaning: Tables and Graphs, Measures of Central Tendency and Dispersion in Frequency Distributions, Probability I: Introductory Ideas, Probability Distributions, Sampling and Sampling Distributions, Estimation, Testing Hypotheses: One Sample Tests, Testing Hypotheses: Two-Sample Tests, Quality and Quality Control, Chi-Square and Analysis of Variance, Simple Regression and Correlation, Multiple Regression and Modeling, Nonparametric Methods, Time Series and Forecasting, Index Numbers, Decision Theory, Appendix Tables, Bibliography, Index.